Paternity and Child Welfare - Nafees Alam (Journal of Forensic Social Work, 2023)
This theoretical and conceptual analysis, rooted and organized by frameworks and empirical literature, aims to explain biases against fathers in the United States’ family court system. Positive paternal involvement has been shown to be correlated with positive child outcomes, placing an emphasis not just on quantity, but quality as well. Despite these findings, fathers are societally expected to be less involved than mothers. Fathers are also in positions to be held financially hostage even when alternatives to pregnancy are legally accessible, suggesting that paternal financial contributions are viable substitutes for paternal involvement. The court of law and the court of public opinion may be in opposition as to where we go from here.